Memahami Karakteristik Peserta Didik Melalui Program Kegiatan Pengenalan Lapangan Persekolahan di SMAS PGRI Maumere - Agnes Afrilarianti; Alsanta Herlina Dahimong; Imelda Ian; Abdullah Muis Kasim (Lembaga Pengembangan Kinerja Dosen, 2025)
This study aims to identify how to understand the characteristics of students through the implementation of the School Field Introduction Activity Program at SMAS PGRI Maumere, as well as analyze the attitude of students during class hours and outside of class hours. This research uses a qualitative method with a narrative approach. Primary data was obtained through interviews with resource persons, while secondary data was collected from relevant references such as journals and theses related to learner characteristics. The data collection techniques used included interviews and observations. Data analysis was conducted through the stages of data reduction, data presentation, and verification. The results show that learning ability, individual potential, the surrounding environment, the use of interesting learning techniques, and effective teaching methods are important aspects in the education process. In addition, students showed the ability to maintain positive relationships and mutual respect both inside and outside the classroom.